Simple, Noninvasive Hemodynamic Monitoring Improves Uncontrolled Hypertension - Hoyle, Brian (MD Conference Express, 2014)
The findings of the multicenter Better Control of Blood Pressure in Hypertensive Patients Monitored Using the HOTMAN System trial [BEAUTY; NCT01482364] of 153 patients has shown the value of the simple and noninvasive monitoring of hemodynamic parameters in improving uncontrolled hypertension.